2011
DOI: 10.1111/j.1462-2920.2011.02474.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of bacteriophage host strains of Bacteroides species suitable for tracking sources of animal faecal pollution in water

Abstract: Microbial source tracking (MST) methods allow the identification of specific faecal sources. The aim is to detect the sources of faecal pollution in a water body to allow targeted, efficient and cost-effective remediation efforts in the catchment. Bacteriophages infecting selected host strains of Bacteroides species are used as markers to track faecal contaminants in water. By using a suitable Bacteroides host from a given faecal origin, it is possible to specifically detect bacteriophages of this faecal origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 39 publications
1
30
0
2
Order By: Relevance
“…Faecal contamination of surface waters poses a major risk to public health, and bacteriophages specific to human faecal indicator bacteria (and the human gut microbiome) have already been successfully employed as water quality indicators that can specifically identify pollution originating from human sources [20][22], [25], [26]. Bacteriophage offer numerous advantages in these applications and are not only thought to persist longer in the environment than host bacteria but can often be found in higher numbers making them a more sensitive source tracking tool [22]. In particular, the development of rapid and sensitive culture-independent methods for detection of human faecal indicator phage, directly in environmental samples, offers significant advantages over classic culture-based approaches, and there is presently much interest in developing and implementing such strategies [27].…”
Section: Introductionmentioning
confidence: 99%
“…Faecal contamination of surface waters poses a major risk to public health, and bacteriophages specific to human faecal indicator bacteria (and the human gut microbiome) have already been successfully employed as water quality indicators that can specifically identify pollution originating from human sources [20][22], [25], [26]. Bacteriophage offer numerous advantages in these applications and are not only thought to persist longer in the environment than host bacteria but can often be found in higher numbers making them a more sensitive source tracking tool [22]. In particular, the development of rapid and sensitive culture-independent methods for detection of human faecal indicator phage, directly in environmental samples, offers significant advantages over classic culture-based approaches, and there is presently much interest in developing and implementing such strategies [27].…”
Section: Introductionmentioning
confidence: 99%
“…They include antibiotic-resistant enterococcus phenotypes (18), bacteriophages of Bacteroides spp. (17,23,38), F-RNA bacteriophage subgroups (21), Rhodococcus coprophilus (41), Bacteroides group (8, 39), Bifidobacterium spp. (3,6,7,11,25,31), and biochemical fingerprinting of bacterial populations (32).…”
mentioning
confidence: 99%
“…A previous study in a river with an intermediate contamination level, which receives inputs from industrial areas and the secondary effluents of municipal wastewater treatment plants, showed a median number of 7·9 PFU 100 ml −1 and a maximum value of 120 PFU 100 ml −1 with 85% positive detection for RYC2056PH (Gómez‐Doñate et al . ). Another study of rivers from Europe and South America revealed that 70% of the samples tested contained RYC2056PH, and the averaged concentrations ranged from below 10 to above 100 PFU 100 ml −1 when stratifying the data based on faecal coliforms levels (Lucena et al .…”
Section: Discussionmentioning
confidence: 97%
“…This group of phages has been found in faecally polluted water bodies, including river water (Araujo et al 1997;Dur an et al 2002), river sediment (Tartera and Jofre 1987), seawater (Contreras-Coll et al 2002;Moc e-Llivina et al 2005) and groundwater . To date, studies of indigenous Bacteroides phages have been conducted in a number of geographical regions, mostly in temperate climates, including those in Mediterranean and European countries (Tartera and Jofre 1987;Araujo et al 1997;Contreras-Coll et al 2002;Dur an et al 2002;Pay an et al 2005;Blanch et al 2006;G omez-Doñate et al 2011;Wicki et al 2011;Muniesa et al 2012), the continental USA (Kator and Rhodes 1992), South Africa (Grabow et al 1995), Hawaii (Vijayavel et al 2010) and South America (Lucena et al 2003). Because different climates could affect microbial behaviours and environmental factors, Bacteroides bacteriophages require further investigations in a wider set of geographical areas, including tropical countries, to ensure their worldwide use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation